Pengembangan Media Pembelajaran Interaktif Berbasis Android dan Efek Terhadap Hasil Belajar Peserta Didik Kelas XI IPS SMA - Cahyaningrum, Marina Nur; Sakti, Norida Canda (Universitas Nusantara PGRI Kediri, 2021)
This research was carried out on the basis of the problem because of the little choice of learning media a teacher uses on economics subjects discussing complex APBN and APBD material. The purpose of this research is to determine the feasibility of the media, find out learners’ response, and learning outcomes of students after the implementation of android-based interactive learning media. This research adopts the 4D development model which only reaches the development stage. This research was conducted on 20 students of class XI social sciences in the 5th Senior High School Tuban by collecting data using interviews and questionnaires that were analyzed through quantitative and qualitative data analyzed. The result is interactive learning media based on android with the APK format APBN and APBD material. The validation result obtained proper conclusions consisting of material expert 100%, media expert 97,5%, evaluation expert 78,67%, media practicality expert 100%, and media effectiveness 100%. Students resulted in positive responses by 97% and can encourage learning outcomes with an average Gain Score 0,72 and completeness of classical posttest attain 95%. So, android based interactive learning media can improve student learning outcomes.